Enhancement of Responsivity in Solar-Blind UV Detector With Back-Gate MOS Structure Fabricated on β-Ga2O3 Films - Meng, Dongdong D.; Ji, Xueqiang Q.; Wang, Dafang F.; Chen, Zhengwei W. (Frontiers in Materials, 2021)
Monoclinic Ga2O3 (β-Ga2O3) film was grown on Si/SiO2 by using MOCVD. Then, we have fabricated the solar-blind photodetector with back-gate MOS structure. The device exhibited obvious photoresponse under 254 nm UV light illumination and the photocurrent could be controlled by VGS. The current generated under dark condition could also be regulated by VGS and tended to constant when the regulation of VGS reaching saturation. Meanwhile, VGS was confirmed to have a certain ability to regulate the photocurrent. The present device demonstrated excellent stability and fast response (rise) and recovery (decay) time under the 254 nm light illumination as well as responsivity of 417.5 A/W, suggesting a valuable application in the solar-blind UV photodetectors.